2022
DOI: 10.3390/ijms23116176
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3 Dioxygenase 1—The Potential Link between the Innate Immunity and the Ischemia-Reperfusion-Induced Acute Kidney Injury?

Abstract: Ischemia-reperfusion injury (IRI) is of the most common causes of acute kidney injury (AKI); nevertheless, the mechanisms responsible for both early kidney injury and the reparative phase are not fully recognised. The inflammatory response following ischemia is characterised by the crosstalk between cells belonging to the innate immune system—dendritic cells (DCs), macrophages, neutrophils, natural killer (NK) cells, and renal tubular epithelial cells (RTECs). A tough inflammatory response can damage the renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 132 publications
0
8
0
Order By: Relevance
“…The key enzyme kynurenine-3-monooxygenase (KMO), responsible for converting KYN to 3-HK in human kidneys, is located on the outer membrane of PTECs (Zheng et al, 2019). After AKI, the activity of the IDO enzyme increases in renal TECs leading to an increase in KP decomposition (Krupa et al, 2022). Studies have shown that the expression of KMO in renal TECs decreases in a dose-dependent manner after treatment with cisplatin, resulting in an increase in KYN entering the KYNA and NAD branch (Tan et al, 2021).…”
Section: Tryptophanmentioning
confidence: 99%
See 1 more Smart Citation
“…The key enzyme kynurenine-3-monooxygenase (KMO), responsible for converting KYN to 3-HK in human kidneys, is located on the outer membrane of PTECs (Zheng et al, 2019). After AKI, the activity of the IDO enzyme increases in renal TECs leading to an increase in KP decomposition (Krupa et al, 2022). Studies have shown that the expression of KMO in renal TECs decreases in a dose-dependent manner after treatment with cisplatin, resulting in an increase in KYN entering the KYNA and NAD branch (Tan et al, 2021).…”
Section: Tryptophanmentioning
confidence: 99%
“…Following AKI onset, the levels of amino acids in renal tubular cells significantly decrease . Up-regulation of IDO enzyme-induced tryptophan depletion can increase the autophagic flux in human renal TECs by activating eukaryotic initiation factor 2 (eIF2α) kinase general control non-derepressible 2 (GCN2) (Fougeray et al, 2012;Krupa et al, 2022). Chaudhary et al (2015) found that increasing renal IDO1 activity or inducing autophagy with GCN2 agonists can protect mice from renal inflammatory injury.…”
Section: Metabolism and Autophagymentioning
confidence: 99%
“…The key enzyme kynurenine-3-monooxygenase (KMO), responsible for converting KYN to 3-HK in human kidneys, is located on the outer membrane of PTECs ( Zheng et al, 2019 ). After AKI, the activity of the IDO enzyme increases in renal TECs leading to an increase in KP decomposition ( Krupa et al, 2022 ). Studies have shown that the expression of KMO in renal TECs decreases in a dose-dependent manner after treatment with cisplatin, resulting in an increase in KYN entering the KYNA and NAD branch ( Tan et al, 2021 ).…”
Section: Energy Metabolism Of Renal Tubular Epithelial Cells In Healt...mentioning
confidence: 99%
“…IDO upregulation leads to the depletion of tryptophan (TRP), which can activate the general control non-derepressible 2 kinases (GCN2K) pathway and inhibit the mammalian target of rapamycin (mTOR) signaling, thereby promoting renal TEC’s apoptosis. Increased IDO activity can also regulate cysteine aspartic protease-8 activation and TECs apoptosis via the Fas/Fas ligand (FasL) -dependent mechanism ( Krupa et al, 2022 ). The metabolism of polyamines produces ROS and reactive aldehyde, which are important inducing factors for DNA damage, mitochondrial damage, endoplasmic reticulum stress/unfolded protein response, and can trigger TEC’s apoptosis and AKI renal tubular injury ( Zahedi et al, 2019 ).…”
Section: Relationship Between Energy Metabolism and Programmed Cell D...mentioning
confidence: 99%
“…L-Trp consumption and Kyn production are key to immune system regulation under both physiological and disease conditions (Maddison and Giorgini, 2015;Barreto et al, 2018;Odunsi et al, 2022). Recent studies have continued to highlight the importance of L-Trp metabolism in immune regulation, neuronal function, and ageing (Sorgdrager et al, 2019;Platten et al, 2021;Krupa et al, 2022;Merlo et al, 2022;Ouyang et al, 2022;Salminen, 2022).…”
Section: Introductionmentioning
confidence: 99%